(untitled) (World Bulletin of Management and Law, 2023)
Acquittals issued by the court, the procedure for their preparation and announcement, making acquittals legal, reasonable, fair and civilized, the main requirements for acquittals - a thorough study of their legality, reasonableness and fairness, and relevant recommendations, opinions on eliminating shortcomings in this regard -consists of expressing opinions